Is social class standardisation appropriate in occupational studies?. Issue 4 (December 1987) - Brisson, C; Loomis, D; Pearce, N
Abstract : Social class standardisation has been proposed as a method for separating the effects of occupation and "social" or "lifestyle" factors in epidemiological studies, by comparing workers in a particular occupation with other workers in the same social class. The validity of this method rests upon two assumptions: (1) that social factors have the same effect in all occupational groups in the same social class, and (2) that other workers in the same social class as the workers being studied are free of occupational risk factors for the disease of interest. These assumptions will not always be satisfied. In particular, the effect of occupation will be underestimated when the comparison group also has job-related exposures which cause the disease under study. Thus, although adjustment for social class may minimise bias due to social factors, it may introduce bias due to unmeasured occupational factors. This difficulty may be magnified when occupational category is used as the measure of social class. Because of this potential bias, adjustment for social class should be done only after careful consideration of the exposures and disease involved and should be based on an appropriate definition of social class. Both crude and standardised results should be presented when such adjustments are made.